JUMLAH SPERMATOSIT PRIMER DAN KADAR TESTOSTERON INTRATESTIKULER PADA TIKUS Sprague Dawley YANG DIINDUKSI STREPTOZOTOCIN DENGAN LATIHAN TERATUR TERUKUR - , dr.Jodelin Muninggar, Prof. Dr.. Sri Kadarsih S., M.Sc., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background :Hyperglycemia often happens in people with diabetesmellitus. It affects on the increase of oxidative stress and the formation of advanceglycationend products. Both have an important role in the chronic complication on the reproductive organs : the testicle. Follicle Stimulating Hormone will stimulate Sertolicells for the spermatogenesis process, while Luteinizing Hormone will stimulate Leydig cells to produce testosterone hormone for the process of spermatogenesis. Growth Hormone/Insulin-like Growth Factor-1 is anautocrin/paracrinfactor in regulating the number and function of the mature Leydig cells. Growth Hormone/Insulin â like Growth Factor-1 serves as the proliferation stimulator and directmitogenic factor in stimulating the germcells proliferation.